Organic carbon and nitrogen mineralization under Mediterranean climatic conditions: the effects of incubation depth - Rovira, P; Vallejo, V R (Soil Biology and Biochemistry, 1997)
n a soil profile, temperature and humidity regimes change with depth. Under Mediterra- nean conditions, upper horizons are more affected by water deficits and drying-rewetting cycles than deep horizons. Our aim was to study how carbon and nitrogen mineralization are affected by depth, and special attention is paid to separating the effects of pedoclimate from the effects of other con- straints like amount and quality of organic matter. To this end, mixtures of plant + soil material were exposed by incorporation in the field, at depths of 5, 20 and 40 cm, in nylon mesh bags. Mineralization of C and N was studied for 2 y. For all types of plant material studied (Eucalyptus globulus, Quercus ibex and Pinus halepensis), mineralization of both carbon and nitrogen was lower at 5cm. No differ- ences were between 20 and 40 cm. This result, probably as a result of the higher drying of the upper- most horizons, contrasts with the usual findings on this topic. The amounts of both C and N mineralized were lower than expected, probably because plant materials were finely ground, allowing stabilization in the mineral matrix of soil. With the possible exception of Pinus, depth affected the rate of mineralization, not the relation between C and N. It is concluded that, at least under Mediterranean conditions, the pedoclimate in deep layers is more favourable to microbial activity than in upper layers, in which drought is a strong limiting factor. Reduced oxygen availability in the subsoil layers did not inhibit decomposition and mineralization to the same extent as did desiccation in the surface layer. The higher mineralization of C and N usually found in upper horizons may be attributed to the higher amount and quality of organic matter in these horizons, rather than to pedoclimatic constraints
Keywords: mineralization; organic matter (voyant); Soil depth; water content